Pemikiran dan Aplikasi Teologi Lingkungan di Pesantren Cicalengka Kabupaten Bandung - Saeful Anwar; Rifki Rosyad (UIN Sunan Gunung Djati Bandung, 2021)
Environmental problems are a technical, ecological problem and environmental theology, seeing how the relationship between the environment and God through the pesantren. This study aims to examine the theological understanding, awareness, and role of the Al-Faaruuq and Bahrul Hidayah Islamic boarding schools in the environment. Christian's research method is descriptive-qualitative to describe several variables relating to the research problem. This study's data sources, namely primary data sourced from information derived from Kiai or Ustaz caretakers of Al-Faaruuq Islamic boarding school and Islamic boarding school Bahrul Hidayah. Meanwhile, this research's secondary data sources are documents (journals, academic research, articles, books, and magazines). This research aims to understand the environmental theology in Islamic boarding schools al-Faaruuq and Islamic boarding school Bahrul Hidayah through the basic principles of ecological theology, namely; 1). Understanding God's unity and His creation (tauhid) are used as guidance and foothold in environmental doctrine, 2). Seeing God's signs (ayat) anywhere through contemplating nature as God's creation, 3). Become a guardian (caliph) on earth by forming the character of his students who are responsible for being caliph. 4). Maintain God's trust (amanah) and care for the environment because it is a mandate and held accountable later 5). Striving to uphold justice ('adl) limiting the use of nature according to needs, 6). Live a life in balance with nature (mizan), namely through harmonizing the human-God-nature relationship.